Blood viscosity increases the degree of coronary stenosis in coronary heart disease (Universa Medicina, 2015)
BackgroundEndothelial dysfunction and associated increased blood viscosity (BV) play an important role in the formation of atherosclerosis during inflammatory processes. C-reactive protein (CRP) is a biomarker of inflammation with an active role in endothelial dysfunction and development of atherosclerosis that is marked by degree of coronary stenosis (CS). The purpose of this study was to determine the relationship of BV and CRP with varying degrees of CS among coronary heart disease (CHD) patients.MethodsThis cross-sectional study involved 24 subjects taken consecutively among patients with CHD who underwent angiography. Blood viscosity levels were determined using an Ostwald viscometer, with reference limits of 1.5 to 1.72 (cP). C-reactive protein was determined by turbidimetric immunoassay, with a normal reference value of